Synthetic access to 3, 4-disubstituted pyroglutamates from tetramate derivatives from serine, allo-threonine and cysteine. Issue 40 (4th October 2019) - Bagum, Halima; Christensen, Kirsten E.; Genov, Miroslav; Pretsch, Alexander; Pretsch, Dagmar; Moloney, Mark G.
Abstract: A route allowing the conversion of substituted tetramates to 3, 4-disubstituted pyroglutamates, making use of Suzuki coupling on an enol mesylate, followed by reduction, is both general and fully stereoselective. Graphical abstract: Image 1